Effectiveness of Internal Communication in Government Bureaucracy: Analysis of Managerial Line Performance - Sjoraida, Diah Fatma (Jurnal EMT KITA, 2025)
The managerial performance of civil servants in Sumedang Regency is actually good, but sometimes there is still unclear messages from the managerial line to subordinates, so that sometimes it happens, which results in ineffective internal communication. The purpose of this research was to determine and analyze the variables of message clarity and communication frequency that affect the performance of the managerial line through communication effectiveness as an intervening variable. The subjects of this research were civil servants in Sumedang Regency, West Java. The variables in this research are independent variables, namely the variables of message clarity and communication frequency, dependent variables, namely the variable of managerial line performance and the intervening variable is the variable of communication effectiveness. The results of data analysis using SEM analysis using SMART PLS 3.0 software. Data collection techniques by observation and giving questionnaires to respondents and literature studies. The results of research then conclude that partially the variables of message clarity and communication frequency influence the performance of the managerial line and the effectiveness of civil servant communication in Sumedang Regency, West Java, the variable of communication effectiveness influences the performance of the managerial line of civil servants in Sumedang Regency, West Java. Simultaneously the variables of message clarity and communication frequency influence the performance of the managerial line of civil servants in Sumedang Regency, West Java through the variable of communication effectiveness as an intervening variable.